PENGARUH LATIHAN INTERVAL SPRINT TERHADAP KECEPATAN LARI PADA SSB SIMPATIG U-15 - Reza Habibie; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: The problem in this research is that it often does not hit when chasing a fast ball, always loses as a result of winning the ball, is not fast when taking a fast ball, with such circumstances the ball originally score against the goal of the opponent, so it is difficult and less likely to score points. The title of this research is "The effect of sprint interval exercises on running speed on SSB Simpatig U-15" so that the future goals for athletes after research can perform much better and above all much better and play and discover whether there is an increase in the ability of athletes running speed in football to keep track of the opponent's game and to achieve maximum results in the future. The form of this study is (with a pretest-post-test design approach of one group) with the population of SSB Simpatig U-15 Pekanbaru players. In the study the sampling technique used is a full sample that is determining the sample if all members of the population are used as samples. The instrument used in this study was to use a 40-meter sprint test, which aims to determine the effect of Sprint interval training on running speed on the SSB Simpatig U-15 Pekanbaru. The data is then statistically processed to test the normality with the help of the lilifours test at a significant level of 0.05α. The proposed hypothesis is that there is an effect of sprint interval training on running speed in the SSB Simpatig U-15 Pekanbaru. Based on the analysis of the normality of the X data, the Lcount was 0.094 and Ltable 0.213, which means that Lcount < Ltable. while the Y variable yields Lcount of 0.161 and Ltable of 0.213. This means Lcount < LTable. Based on statistical data analysis, there is an average variable X 5.65 and an average variable Y of 5.65, after which the data is normally distributed. So it can be concluded that for the effect of the variable x with the obtained variable y the value of t = 2.666 and tcount > ttable (2.666) > (1.753), then Ha is accepted, in other words, there is a significant influence on the sprint interval training on running speed on the SSB Simpatig U-15.Key Words: Sprint Interval Training, Running Speed